Character Education in Science Learning Based on Islamic Civilization at Madrasah - Karep; Dadang (Postgraduate, University of Mataram, 2025)
This study explores the integration of character education in science (IPA) learning based on Islamic civilization at MAN 1 Ogan Komering Ulu Selatan. The research aims to analyze how Islamic values and the legacy of Muslim scholars are embedded in science instruction to foster students’ moral and intellectual development. Using a qualitative descriptive approach, data were collected through interviews with teachers, students, and school leaders, classroom observations, and document analysis. The findings reveal that the integration of ayat kauniyah, the contributions of Muslim scientists such as Al-Jazari and Banu Musa, and value-based practices effectively promote character traits including religiosity, honesty, responsibility, and environmental awareness. Teaching strategies such as storytelling, role modeling, and habituation support the internalization of Islamic values within the science curriculum. However, challenges persist, including limited teacher capacity, inadequate learning resources, insufficient facilities, and low parental involvement. The study concludes that a holistic, tawhid-based approach to science education can cultivate insan kamil—individuals who are both scientifically competent and morally upright.